Metal concentrations in the shell of Bathymodiolus azoricus from contrasting hydrothermal vent fields on the mid-Atlantic ridge - Cravo, Alexandra (2020)
Specimens of Bathymodiolus azoricus were sampled along the Mid-Atlantic Ridge at the Menez Gwen, Lucky Strike and Rainbow hydrothermal fields. Individual shells (n = 51), through the weight range 0.62 to 15.70 g, were analyzed for their magnesium, strontium, iron, manganese, copper, zinc and cadmium concentrations. Amongst the marine molluscs the shell of B. azoricus is confirmed as being particularly impoverished in strontium (mean 943 microg g(-1)). Trace metal concentrations in the shells decreased in the order Fe> Mn> Zn> Cu> Cd. Despite originating from trace metal rich environments mean concentrations were low (37.9, 13.2, 10.7, 1.1 and 0.7 microg g(-1), respectively). Irrespective of geographical origin magnesium, strontium and copper concentrations were primarily dictated by shell weight. In contrast cadmium concentrations were elevated in shells from the Rainbow field and ambient seawater chemistry imparted site specific chemical fingerprints to the shells with respect to the iron to manganese ratio.